A comparative research of the fresh fruit bunch productivity between three-wheeler machine and buffalo assisted in-field collection in Muadzam, Pahang, Malaysia - Nazari, N; Saili, A R; Zulkefli, F; Syahlan, S (Nurture, 2023)
Background: Malaysia’s palm oil exports may experience a steady increase due to the ongoing Russia-Ukraine conflict. Although the demand for palm oil is increasing, there is still a significant labor shortage in the plantation industry. As a result, the use of machinery has become a key component in Malaysia’s oil palm plantation industries, particularly for in-field collection. Purpose: The purpose of this study is to evaluate the performance of a three-wheeler machine and BAIC as a harvesting mechanization in the oil palm estate. Design/Methodology/Approach: This study involved a time and motion study to make a comparison between the performance of a three-wheeler machine and BAIC. Findings: The trials proved that the total average productivity for three-wheeler machines and BAIC is 12.81 mt/day and 4.55 mt/day, respectively. Additionally, the average productivity for each harvester that uses a three-wheeler machine is 3.2 MT/day/harvester, while for BAIC it is 2.27 MT/day/harvester. The cost-effectiveness of a three-wheeler machine is MYR 7.28/mt/harvester, while for BAIC it is MYR 1.41/mt/harvester (MYR = Malaysian Ringgit). Conclusion: The use of a three-wheeler machine has been proven to increase the productivity of FFBs. Although using a three-wheeler machine requires more caution, it really makes the in-field collection process for labour much easier for the laborers, ultimately improving productivity rates and increasing laborers’ pay. Research Limitations: It is quite difficult to find an estate that still uses buffalo for in-field collection because most of the estates have switched to machinery. Practical Implications: This research can be used as a reference and guidelines to improve estate management and ensures the sustainability of the oil palm industry around the world. Contribution to Literature: The literature on BAIC will be expanded by this study, particularly in the area of oil palm plantations.